Goal-driven reasoning overcomes cell D neglect in contingency judgements - Mata, André; Garcia-Marques, Leonel; Ferreira, Mário B.; Mendonça, Cristina (Journal of cognitive psychology, 2015)
Research on contingency judgement typically shows cell weight inequality such that the information in cell A of a contingency table is considered more relevant than the information in cell D, even though both kinds of information have the same confirmatory meaning. Two studies tested whether goal-driven reasoning can lead people to realise the value of the information in cell D. Participants' goal to defend a particular conclusion for which the information in cell D was helpful was manipulated. Whereas participants who did not have that goal displayed the usual cell D neglect, goal-driven participants for whom cell D contained goal-relevant information considered it important. More importantly, in subsequent tasks with different contents where participants were no longer driven by any goal, they continued to consider information in cell D relevant (Study 1), and they were more likely to make correct contingency judgements, which depended on considering cell D (Study 2).